The Role of Specific Diet on the Treatment of Pediatric Asymptomatic Microscopic Hematuria; a Before and After Study: Specific Diet on Microscopic Hematuria - Koochaki, Reyhaneh; Mohkam, Masoumeh (Journal of Pediatric Nephrology, 2020)
Background and Aim: Asymptomatic microscopic hematuria (AMH) in children has been known as a troublesome clinical condition which demands a patient to visit a physician. This study aimed to investigate the role of a specific diet on the amelioration of AMH in children. Methods: The current analysis was carried out in children ranging from 6 months to 14 years. This before and after research study was performed to evaluate the effects of certain diet on the treatment of pediatric AMH. Renal function tests, kidney ultrasonography and urinary assessments were performed and patients with AMH were enrolled in this query. Study group was ordered to consume a specific hypoallergenic diet. The number of urinary red blood cells was compared before and after diet. Data were analyzed using SPSS. A value of P < 0.05 was considered significant. Results: Our special diet was effective in the treatment of stable microscopic hematuria in 72% of study group. Statistically, after a special diet, there was a significant decrease in the number of red blood cells in urine test (P <0.001). Conclusion: Specific hypoallergenic diet was effective in treatment of AMH in children. Reducing urinary red blood cell counts has been linked to the effectiveness of diet in the management of stable microscopic hematuria.